Fuel Property Investigation: Jatropha Biodiesel, Used Cooking Oil Biodiesel and Fuel-grade Ethanol Blends. Issue 1 (May 2021) - Sahu, Tomesh Kumar; Shukla, Pravesh Chandra; Sahu, Vikas Kumar; Gupta, Satyajit; Sarkar, Sumit
Abstract: Compression ignition (CI) engines are one of the promising power producing units which provide higher efficiency and durability. Increasing environmental pollution and depleting resources led the research in the field of alternative fuels such as biodiesels, ethanol etc. for utilization in CI engines. In the present study, two different types of biodiesels i.e. Jatropha Biodiesel (JBD), Used Cooking Oil (UCO) Biodiesel and Ethanol were investigated for the fuel properties and compared. Various fuel properties like density, kinematic viscosity, calorific value, oxidation stability, cold weather properties (CFPP, CF, and PP), and flash point temperature were measured and compared for pure form of alternative fuels. Different blends (5%, 10%, 15% and 20%) of JBD, UCO biodiesel and ethanol were also investigated. It has been observed that ethanol showed lower density, lower viscosity and superior cold weather properties compared to the tested fuels/blends. The average viscosity for ethanol was measured to be 1.08 mm2/sec which is ∼61.8 % less compared to mineral diesel. Oxidation stability tests were also performed where mineral diesel shows 83.15 min for 10% pressure drop at 140°C and 700 kPa, UCO biodiesel and JBD shows 9.2 min and 8.32 min. 5% ethanol blend showed sharp reduction in flash point compared to mineral diesel, however, it remained almost at the same level with further blending.